SYNTHESIS AND ANTIMICROBIAL ACTIVITY EVALUATION OF SOME SCHIFF BASES DERIVED FROM 2-AMINOTHIAZOLE DERIVATIVES - Gupta, Rajul; Fuloria, Neeraj Kumar; Fuloria, Shivkanya (Indonesian Journal of Pharmacy, 2013)
Various substituted acetophenones (1-5) on treatment with iodine and thiourea yielded 2-amino-4-(substituted-phenyl)thiazole (1a-5a), which on further treatment with various substituted aldehydes to get N-(substitutedbenzylidene)-4(substitutedphenyl)thiazol-2-amine (1b-5b). All the synthesized compounds were characterized by their respective FTIR, H NMR and Mass data. Synthesized compounds (1b-5b) were subjected to investigation for their antibacterial and antifungal studies against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Candida albicans, Asperigillus flavus and Asperigillus fumigatus by disk diffusion method. Compound 5b was found to be most effective with largest zone of inhibition. Key words: Thiazole, Acetophenones Antibacterial, Antifungal, Substituted Aldehydes.